(untitled) (GYMNASIUM, 2017)
Extreme sports acquired more and more of the tourism market in Romania. Tourists seek the adventure, adrenaline, limit, risk, courage, and challenge. The long walks, the visits to ancient vestiges or to museums are all part of the past tourism. Today, the rafting, diving, jumping, paragliding, canyoning and Tyrolean traverse are in trend.